The Function of Bio-invigoration Based on Rhizobacteria in Promoting Shallot (Allium cepa L.) Growth in Saline Soil - Ni Wayan Hesthin; Gusti Ayu Kade Sutariati; Tresjia Corina Rakian; I Kadek Pande Prasetia; Jendri Mamangkey (International Journal of Science and Environment (IJSE), 2026)
Shallots are an important commodity whose productivity is often constrained by the use of low-vigor seeds and saline soil conditions. This study aimed to examine the effect of seed bio-invigoration using rhizobacteria and the composition of saline soil media on shallot growth. The study employed a randomized block design with two factors, namely bio-invigoration (no treatment, KLK 05 isolate, and KNU 13 isolate) and saline soil media composition (100%, 75%, 50%, and 25% combined with organic fertilizer). The observed variables included plant height, number of leaves, number of tillers, leaf area, and root length. The results showed that bio-invigoration and the addition of organic fertilizer significantly improved plant growth. The combination of rhizobacteria with moderate to low salinity media produced the best results through increased nutrient uptake, ion balance, and vegetative growth. Therefore, bio-invigoration and organic fertilizer have the potential to be effective strategies for improving shallot growth in saline soils.